Frugal Living and Family Financial Management: The Pivotal Role of Housewives - Dewi, Made Diah Chandra; Atmadja, Anantawikrama Tungga; Adiputra, I Made Pradana (Journal of Social Work and Science Education, 2025)
This research aims to determine the role of housewives in managing finances by living frugally and the implications for family welfare. The method used in this research is a qualitative method that explores the role of housewives in implementing frugal living to manage family finances, using interviews and observations with employees at Puri Raharja Hospital, Denpasar. Based on the research results, the findings revealed three motivations for living frugally: economic stability, psychological well-being, and saving for children’s education. Housewives serve as financial managers, decision makers, and educators, encouraging spending discipline and long-term savings. This study highlights the positive implications of frugal living on family well-being and gender equality, and emphasizes its potential as a sustainable financial strategy. The limitation of this research is the research design which was only carried out in one place, thus suggesting that there should be more extensive research in the future.